Perinatal management of trisomy 18: a survey of obstetricians in Australia, New Zealand and the UK. (30th October 2013) - Wilkinson, D. J. C.; de, L.; Lees, C.; Savulescu, J.; Thiele, P.; Tran, T.; Watkins, A.
ABSTRACT Objective The objective of this study was to explore the attitudes of obstetricians in Australia, New Zealand and the UK towards prenatally diagnosed trisomy 18 (T18). Method Obstetricians were contacted by email and invited to participate in an anonymous electronic survey. Results Survey responses were obtained from 1018/3717 (27%) practicing obstetricians/gynaecologists. Most (60%) had managed a case of T18 in the last 2 years. Eighty‐five per cent believed that T18 was a 'lethal malformation', although 38% expected at least half of liveborn infants to survive for more than 1 week. Twenty‐one per cent indicated that a vegetative existence was the best developmental outcome for surviving children. In a case of antenatally diagnosed T18, 95% of obstetricians would provide a mother with the option of termination. If requested, 99% would provide maternal‐focused obstetric care (aimed at maternal wellbeing rather than fetal survival), whereas 80% would provide fetal‐oriented obstetric care (to maximise fetal survival). Twenty‐eight per cent would never discuss the option of caesarean; 21% would always discuss this option. Management options, attitudes and knowledge of T18 were associated with location, practice type, gender and religion of obstetricians. Conclusion There is variability in obstetricians' attitudes towards T18, with significant implications for management of affected pregnancies. © 2013 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd.